The “Visual Shock” of Francis Bacon: an essay in neuroesthetics - Zeki, Semir; Ishizu, Tomohiro (Frontiers in Human Neuroscience, 2013)
In this paper we discuss the work of Francis Bacon in the context of his declared aim of giving a “visual shock”. We explore what this means in terms of brain activity and what insights into the brain’s visual perceptive system his work gives. We do so especially with reference to the representation of faces and bodies in the human visual brain. We discuss the evidence that shows that both these categories of stimuli have a very privileged status in visual perception, compared to the perception of other stimuli, including man-made artifacts such as houses, chairs and cars. We show that viewing face and house stimuli that depart significantly from a normal representation of faces and bodies entails a significant difference in the pattern of brain activation. We argue that Bacon succeeded in delivering his” visual shock” because he subverted the normal neural representation of faces and bodies, without at the same time subverting the representation of man-made artifacts.